The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/frvir.2022.846490
|View full text |Cite
|
Sign up to set email alerts
|

Breaking immersion: A theoretical framework of alienated play to facilitate critical reflection on interactive media

Abstract: There is a growing interest in understanding how to best represent complexity using IDNs. We conceptualize this as the aim to make players of such IDNs reflect critically on the complexity being represented. We argue that current understandings of player experience do not lend themselves to this aim. Research on interactive media has assumed immersion to be a universal positive for the player experience. However, in this article we argue that immersion into the Magic Circle of an IDN could be antagonistic to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, working towards a shared understanding of what makes games work for educational contexts could elevate the field. The recent literature review on how game design makes players critically reflect on the games they play is an example of such a library of game design choices [67]. However, due to only three out of 23 studies assessing motivation, we found the evaluation of digital games as an intrinsically motivated activity primarily lacking.…”
Section: Effectiveness Of Dgbl In Promoting Knowledge Acquisitionmentioning
confidence: 93%
“…However, working towards a shared understanding of what makes games work for educational contexts could elevate the field. The recent literature review on how game design makes players critically reflect on the games they play is an example of such a library of game design choices [67]. However, due to only three out of 23 studies assessing motivation, we found the evaluation of digital games as an intrinsically motivated activity primarily lacking.…”
Section: Effectiveness Of Dgbl In Promoting Knowledge Acquisitionmentioning
confidence: 93%
“…In addition to these scale versions, Haider et al [25] developed the PXI bench, an online tool for the analysis and comparison of PXI response data, which can be accessed on the PXI's official website. 1 However, no additional investigation into the psychometric quality of the PXI has occurred since the original validation. Thus, there is a need for additional validation of the PXI to see if the initial evidence for the scale's quality can be reproduced.…”
Section: Construct Definitionmentioning
confidence: 99%
“…This warrants further theoretical and methodological investigation of whether a lack of awareness of one's surroundings is an aspect of immersion or should constitute an alternative construct, such as absorption. Although recent literature has attempted to increase the clarity for the immersion construct [1] and other similar constructs concerning psychological absorption in a task [34], there remains more work to be done in regards to a more consistent definition of what immersion entails.…”
Section: Challenges Of the Immersion Constructmentioning
confidence: 99%